Pengaruh Jangka Waktu Pinjaman, Tingkat Suku Bunga dan Pengendalian Internal terhadap Kredit Macet pada LPD di Kecamatan Kuta Selatan - Ni Komang Feby Utami; Ni Wayan Yulianita Dewi (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study aims to determine the effect of partial loan tenure, interest rates and internal control on bad credit. The research method used is a quantitative method. The object of this research is the Village Credit Institution in South Kuta District. The subjects of this study were the chairman, treasurer and credit department. LPD in South Kuta sub-district. The research data were collected using a questionnaire. Data analysis was performed using regression analysis. The results showed that the loan period and internal control partially had a negative effect on bad credit and the interest rate partially had a positive effect on bad credit.